2019
DOI: 10.3747/pdi.2019.00041
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Clinical Outcomes of Lupus Nephritis Patients Undergoing Peritoneal Dialysis: A Matched, Case-Control Study

Abstract: The long-term clinical outcomes of peritoneal dialysis (PD) for patients with lupus nephritis (LN) have not been well researched. In the present study, we investigated the long-term prognosis of a Chinese PD cohort. This was a retrospective case-control study that included LN patients receiving PD treatment for more than 90 days from January 2006 to December 2012. Non-diabetic control patients were selected using a ratio of 1:2 for age- and gender-matching. The primary outcome was all-cause mortality. Secondar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…Ye et al demonstrated that the primary pathogens of patients with SLE were Streptococcus pneumonia, Haemophilus influenzae, Pseudomonas aeruginosa, and Staphylococcus aureus. 28 infection pathogens in their study were bacteria and fungi. The main infecting bacteria were Staphylococcus aureus, Pseudomonas aeruginosa, and Escherichia coli.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Ye et al demonstrated that the primary pathogens of patients with SLE were Streptococcus pneumonia, Haemophilus influenzae, Pseudomonas aeruginosa, and Staphylococcus aureus. 28 infection pathogens in their study were bacteria and fungi. The main infecting bacteria were Staphylococcus aureus, Pseudomonas aeruginosa, and Escherichia coli.…”
Section: Discussionmentioning
confidence: 98%
“…demonstrated that the primary pathogens of patients with SLE were Streptococcus pneumonia , Haemophilus influenzae , Pseudomonas aeruginosa , and Staphylococcus aureus . 28 Lin et al. claimed that the most common infection pathogens in their study were bacteria and fungi.…”
Section: Discussionmentioning
confidence: 99%